Occurrence of pharmaceutical, recreational and psychotropic drug residues in surface water on the northern Antarctic Peninsula region - González-Alonso, Silvia; Moreno Merino, Luis; Esteban, Sara; López de Alda, Miren; Barceló, Damià; Durán Valsero, Juan José; López Martínez, Jerónimo; Aceña, Jaume; Pérez, Sandra; Mastroianni, Nicola; Silva Buso, Adrián; Catalá, Myriam; et al. (Environmental Pollution, 2017)
Human presence in the Antarctic is increasing due to research activities and the rise in tourism. These activities contribute a number of potentially hazardous substances. The aim of this study is to conduct the first characterisation of the pharmaceuticals and recreational drugs present in the northern Antarctic Peninsula region, and to assess the potential environmental risk they pose to the environment. The study consisted of a single sampling of ten water samples from different sources, including streams, ponds, glacier drains, and a wastewater discharge into the sea. Twenty-five selected pharmaceuticals and 21 recreational drugs were analysed. The highest concentrations were found for the analgesics acetaminophen (48.74 μg L−1), diclofenac (15.09 μg L−1) and ibuprofen (10.05 μg L−1), and for the stimulant caffeine (71.33 μg L−1). All these substances were detected in waters that were discharged directly into the ocean without any prior purification processes. The hazard quotient (HQ) values for ibuprofen, diclofenac and acetaminophen were far in excess of 10 at several sampling points. The concentrations of each substance measured and used as measured environmental concentration values for the HQ calculations are based on a one-time sampling. The Toxic Unit values indicate that analgesics and anti-inflammatories are the therapeutic group responsible for the highest toxic burden. This study is the first to analyse a wide range of substances and to determine the presence of pharmaceuticals and psychotropic drugs in the Antarctic Peninsula region. We believe it can serve as a starting point to focus attention on the need for continued environmental monitoring of these substances in the water cycle, especially in protected regions such as the Antarctic. This will determine whether pharmaceuticals and recreational drugs are hazardous to the environment and, if so, can be used as the basis for risk-assessment studies to prioritise the exposure to risk. Research Group and Teaching in Environmental Toxicology and ...